2023
DOI: 10.46827/ejes.v10i5.4770
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Concepts and Phenomena in Early Chidhood Science Education: A Literature Review

Abstract: In the current study, an attempt is made to bring together and synthesize research data on the way early childhood children approach thermal phenomena and concepts. In this pool of data, the mental representations of young children, the barriers to the conceptualization of these phenomena and the effectiveness of specialized teaching interventions are highlighted and discussed. Going through a series of empirical studies the paper focuses on critical aspects of thermal phenomena and concepts such as thermal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…This small-scale research study shows that children have developed representations that are compatible with scientifically accepted knowledge, but it is left open that a systematic didactic exploratory approach over time can help children co-construct concepts related to temperature (Ioannou et al, 2023;Kampeza et al, 2016). In the present study, it was observed that children, through free exploration, developed reasoning in their attempt to approach the concept of temperature.…”
Section: Discussionmentioning
confidence: 53%
“…This small-scale research study shows that children have developed representations that are compatible with scientifically accepted knowledge, but it is left open that a systematic didactic exploratory approach over time can help children co-construct concepts related to temperature (Ioannou et al, 2023;Kampeza et al, 2016). In the present study, it was observed that children, through free exploration, developed reasoning in their attempt to approach the concept of temperature.…”
Section: Discussionmentioning
confidence: 53%
“…Among these, the issue of early approach to the natural world and the initiation of children aged 3-8 years into the phenomena and concepts that are thoroughly examined in science at higher education grades emerged as an important field of research. Along this framework, research with multiple orientations and dimensions is carried out with an aim to cover diverse thematic areas such as the difficulties of young children's thinking (Christidou & Hatzinikita, 2006;Convertini, 2021;Ioannou et al, 2023;López-Banet et al, 2022;Vidal Carulla & Adbo, 2020), the basic studies and continuing education of teachers (Corni et al, 2019;Draganoudi et al, 2023) the curricula and appropriate educational materials as well as the use of digital technologies (Kalogiannakis & Papadakis, 2019;Kalogiannakis et al, 2018), the non-formal education institutions (Kornelaki & Plakitsi, 2018;Parissi et al, 2019;Salvatierra & Cabello, 2022), the exploration of science education in the wilderness of special education spectrum (Kaliampos, 2021;Katsidima et al, 2023), etc. The set of these dimensions has gradually synthesized a particular scientific field that is internationally recognized as Early Childhood Science Education (Akerson, 2019;Flores-Camacho et al, 2023;Ravanis, 2022;Siry et al, 2023).…”
Section: Introductionmentioning
confidence: 99%